Forgiveness and the Novelty of Christian Ethics - Errington, Andrew (Modern theology, 2023)
Christian faith, and particularly Christian Ethics, must wrestle with the questions of novelty and continuity posed by Scripture's declaration that a new thing has occurred with the advent of Jesus Christ. The contrasting perspectives on the Law by Thomas Aquinas and Herman Bavinck focus these questions and suggest that forgiveness is an important point of reference for answering them. The importance of forgiveness in Christ's moral teaching suggests that Christian Ethics is marked out by a distinctive awareness of time. The impact of this reorganisation is already apparent in many places in the New Testament, including the posture we see taken towards political authority.